Exploring the Influence of Parental Occupation and Student Creativity on Entrepreneurial Interest Among Vocational Students - ., Rahmatullah; ., Inanna; Supatminingsih, Tuti; ., Sahade; ., Mustari (KnE Social Sciences, 2024)
This study aims to determine the interest in entrepreneurship in vocational students who are influenced by the work background of parents and student creativity which is the purpose of this research, using a quantitative approach. Observation methods, questionnaires and documentation were carried out for the data collection method and the entire sample used was 79 students. Data were analyzed using two way ANOVA test, simple correlation test, and ANACOVA test. The results of the study show that parents’ work background significantly influences the interest in entrepreneurship. These results illustrate where parents with entrepreneurial work backgrounds have a positive impact on students’ interest in entrepreneurship, because entrepreneurial parents generally have a tendency to evaluate higher entrepreneurship. Student creativity has a significant influence on the interest in entrepreneurship. Entrepreneurial interest is significantly influenced by parents’ work background and students’ creativity. This shows that these two factors play an important role in shaping students’ interest in entrepreneurship. SMK as a formal educational institution has a role in increasing student entrepreneurial creativity by maximizing teaching and learning activities and strengthening job training and entrepreneurship training. Keywords: parents’ work background, student creativity, entrepreneurial interest